Therapy-related clonal cytopenia as a precursor to therapy-related myeloid neoplasms - Mithun Vinod Shah; Abhishek A. Mangaonkar; Kebede H. Begna; Hassan B. Alkhateeb; Patricia Greipp; Ahmad Nanaa; Michelle A. Elliott; William J. Hogan; Mark R. Litzow; Kristen McCullough; Ayalew Tefferi; Naseema Gangat; et al. (Blood Cancer Journal, 2022)
Abstract Therapy-related myeloid neoplasms (t-MN) are aggressive leukemia that develops as a complication of prior exposure to DNA-damaging agents. Clonal cytopenia of undetermined significance (CCUS) is a precursor of de novo myeloid neoplasms. Characteristics of CCUS that develop following cytotoxic therapies (therapy-related clonal cytopenia, t-CC) and outcomes following t-CC have not been described. We identified 33 patients with t-CC and compared to a cohort of the WHO-defined t-MN (n = 309). t-CC had a distinct genetic and cytogenetic profile: pathogenic variants (PV) in TET2 and SRSF2 were enriched in t-CC, whereas TP53 PV was more common in t-MN. Ten (30%) t-CC patients developed a subsequent t-MN, with a cumulative incidence of 13%, 23%, and 50% at 6 months, 1, and 5 years, respectively. At t-MN progression, 44% of evaluable patients had identifiable clonal evolution. The median survival following t-CC was significantly superior compared all t-MN phenotype including t-MDS with <5% bone marrow blasts (124.5 vs. 16.3 months, P < 0.001) respectively. The presence of cytogenetic abnormality and the absence of variants in DNMT3A, TET2, or ASXL1 (DTA-genes) were associated with a higher likelihood of developing a subsequent t-MN and an inferior survival. We describe a putative precursor entity of t-MN with distinct features and outcomes.